Pembrolizumab plus lenvatinib in advanced endometrial cancer: case report and systematic review of lung toxicity - Staropoli, Nicoletta; Salvino, Angela; Falcone, Federica; Farenza, Valentina; Costa, Martina; Rossini, Giacomo; Manti, Francesco; Crispino, Antonella; Riillo, Caterina; Ciliberto, Domenico; Arbitrio, Mariamena; Tassone, Pierfrancesco; et al. (Frontiers in Oncology, 2023)
Background The optimal strategy for the treatment of recurrent and/or advanced endometrial cancer is still undefined. Recently, despite the lack of any predictive biomarker, the combination of pembrolizumab with lenvatinib has improved survival outcomes. We here report the long-term management of lung toxicity in a patient with endometrial cancer, and we critically review the current therapeutic options for this disease. Results A patient with heavily pretreated endometrial cancer took pembrolizumab plus lenvatinib for 1 year, achieving a persistent partial response with a time to treatment failure of 18 months, despite relevant lung toxicity that did not affect the remarkable overall clinical benefit. A systematic review of this combination underlines the efficacy outcome despite toxicity. Interestingly, the literature review on lung toxicity suggested the role of anti-angiogenetic agents in the pathogenesis of lung cavitation, probably related to direct treatment activity, and disclosed a potential radiological sign predictive of the activity of anti-angiogenetic agents. Conclusion We underline the efficacy of pembrolizumab plus lenvatinib in the current treatment landscape of endometrial cancer, underscoring the relevance of a correct management of toxicity.